Nurses’ mental health during the covid-19 outbreak: a cross-sectional study - Sampaio, Francisco (2020)
Objective: To describe nurses’ mental health status during the Covid-19 outbreak and to explore the factors that might accentuate the negative consequences on their mental health. Methods: We conducted an online survey to evaluate demographic variables, working conditions, family dynamics, and mental health variables in nurses working in healthcare settings, in Portugal, during the Covid-19 outbreak. Results: Portuguese nurses presented higher depression, anxiety and stress levels, when compared to the Portuguese general population, during the outbreak. Overall, nurses who did not consider the quantity and quality of personal protective equipment as adequate presented significantly higher levels of depression, anxiety, and stress. Conclusions: Our results suggest that nurses’ mental health status seems to be particularly affected by the Covid-19 outbreak and that some modifiable elements might accentuate the impacts on their mental health.